TI_GERICHTE 12.2021.94 vom 16. Februar 2022 , Banca - contratto di consulenza agli investimenti- calcolo del danno - TI Tribunale d'appello (2022)
Banca - contratto di consulenza agli investimenti- calcolo del danno